(untitled) (Journal of Economic Research & Business Administration, 2018)
To form a competitive national economy, it is absolutely necessary to develop an effective investment management system. Due to this, the authors attempted to investigate the process of attracting a flow of foreign direct investment (FDI) to Kazakhstan. Analytical data of the Committee on Statistics of the Republic of Kazakhstan and the UN Committee on Trade and Development were used for analysis. In addition, the article also considers the attraction of FDI in the CIS region. A meaningful analysis of the data made it possible to identify priority sectors that are of interest to foreign investors in the economy of Kazakhstan, as well as projects that contribute to the growth of FDI in the republic. The authors believe that it is necessary to implement the most effective investment policy, which, on the one hand, contributes to the development of the scientific and engineering potential of the country, the development of small and medium-sized businesses, and on the other hand, is aimed to ensure innovative development of industries and regions, to strengthen the infrastructure of innovation clusters . The practical significance of this analysis is to ensure a favourable investment climate and to identify ways to improve the regulation of investment flows in Kazakhstan.